2016
DOI: 10.1002/cam4.690
|View full text |Cite
|
Sign up to set email alerts
|

Role of cancer stem cells in racial disparity in colorectal cancer

Abstract: Although African‐Americans (AAs) have a higher incidence of colorectal cancer (CRC) than White people, the underlying biochemical mechanisms for this increase are poorly understood. The current investigation was undertaken to examine whether differences in self‐renewing cancer stem/stem‐like cells (CSCs) in the colonic mucosa, whose stemness is regulated by certain microRNAs (miRs), could partly be responsible for the racial disparity in CRC. The study contains 53 AAs and 47 White people. We found the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…All these observations have been extended to human cancer cell lines. Precisely, CACO2, SW480, SW620, HT29, and HCT116 cells derived from human colorectal tumors displayed higher levels of total PVT1 compared to NCM460, FHC and HCoEpiC normal colonic epithelial cells (67,70,72,81). Likewise, AGS, MKN45, SGC7901, and BGC823 gastric cancer cell lines have higher PVT1 expression compared to GES1 normal gastric epithelium cell line (76,79).…”
Section: Pvt1 Expression In Normal and Tumor Tissuementioning
confidence: 94%
See 2 more Smart Citations
“…All these observations have been extended to human cancer cell lines. Precisely, CACO2, SW480, SW620, HT29, and HCT116 cells derived from human colorectal tumors displayed higher levels of total PVT1 compared to NCM460, FHC and HCoEpiC normal colonic epithelial cells (67,70,72,81). Likewise, AGS, MKN45, SGC7901, and BGC823 gastric cancer cell lines have higher PVT1 expression compared to GES1 normal gastric epithelium cell line (76,79).…”
Section: Pvt1 Expression In Normal and Tumor Tissuementioning
confidence: 94%
“…The role of PVT1-encoded miRNAs in the initiation and/or progression of malignancies in the stomach or colon is uncertain due to the lack of literature. Only miR-1207 is reported to have an effect in gastric cancer proliferation and invasion, or in the stemness properties of colon cancer cells (52,81). Specifically, it has been shown how ectopic expression of miR-1207-5p in the SGC7901 gastric tumor cell line is able to reduce proliferation and invasion in vitro and in vivo by targeting the catalytic subunit of the telomerase complex hTERT (52).…”
Section: Oncogenic Pvt1 Functions In Colorectal and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another study with colorectal cancer patients (53 AA and 47 CA), not only found an evidence of miRNAs, but also of cancer stem cells and long noncoding RNA PVT1, the host for miR-1207-5p, in cancer racial disparity. AA patients had significantly high levels of miR-1207-5p, which was mechanistically linked to increased ‘stemness’, as evidenced by increase in various markers of cancer stem cells and EMT [151]. This increase in cancer stem cells can possibly explain the relatively aggressive colorectal cancers in AA patients.…”
Section: Epigenetics In Cancer Health Disparitiesmentioning
confidence: 99%
“…CSCs may lead to recurrence, drug-resistance and tumor formation in HCC (5). Cluster of differentiation (CD)133 is a membrane-bound pentaspan glycoprotein that has been identified as a surface biomarker in a variety of cancer types, including breast, colon, prostate, pancreatic, lung and liver carcinoma (2,3,(6)(7)(8)(9)(10)(11). Although its function remains unclear, directly targeting CD133 has been demonstrated to be a potentially effective strategy for eliminating CSCs (11,12).…”
Section: Introductionmentioning
confidence: 99%